2018
DOI: 10.1016/j.bbadis.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

LIFR promotes tumor angiogenesis by up-regulating IL-8 levels in colorectal cancer

Abstract: Leukemia inhibitory factor receptor (LIFR) has been documented as a cancer promoter and to be present at high levels in various types of tumor tissues. In our search for molecules prognostic of colorectal cancer (CRC), we found high levels of LIFR in CRC tissue samples. Further analyses revealed that LIFR was indeed prognostic of CRC patient survival, and was associated with tumor size, lymphatic metastasis and stages. LIFR was found to promote tumor growth, metastasis and angiogenesis both in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…67 candidate marker genes were identified that strongly correlated with the human BP/bRG population (Pollen et al, 2014, 2015). Genes were highlighted related to extracellular matrix formation, migration and stemness, including TNC (Garcion et al, 2004), PTPRZ1 (Baldauf et al, 2015), FAM107A (Kiwerska et al, 2017), HOPX (Yap et al, 2016), and LIFR (Wu et al, 2018). Importantly, LIFR/STAT3 signaling was found to be required for bRG cell cycle progression and selectively expressed by bRGs (Pollen et al, 2015).…”
Section: Characteristics Of Brgsmentioning
confidence: 99%
“…67 candidate marker genes were identified that strongly correlated with the human BP/bRG population (Pollen et al, 2014, 2015). Genes were highlighted related to extracellular matrix formation, migration and stemness, including TNC (Garcion et al, 2004), PTPRZ1 (Baldauf et al, 2015), FAM107A (Kiwerska et al, 2017), HOPX (Yap et al, 2016), and LIFR (Wu et al, 2018). Importantly, LIFR/STAT3 signaling was found to be required for bRG cell cycle progression and selectively expressed by bRGs (Pollen et al, 2015).…”
Section: Characteristics Of Brgsmentioning
confidence: 99%
“…The most frequent pairs that appeared in at least 4 types of cancer were shown in Table 2. These common critical pairs could contribute to aberrant cell growth, survival and cell motility in various cancer types [3840]. MiR-21 was the most common miRNA that was found in many critical miRNA-target gene pairs [37, 41].…”
Section: Resultsmentioning
confidence: 99%
“…In breast cancer, LIFR has been identified as a tumor suppressor and a negative regulator of YAP 29 . On the other hand, LIFR has been shown to promote tumor progression in prostate cancer 30 , melanoma 31 , and colorectal cancer 32 . More recently, LIFR signaling has been implicated in breast cancer cell dormancy in bone marrow 33 .…”
Section: Introductionmentioning
confidence: 99%